2013
DOI: 10.1021/jz401985k
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Ultrafast Charge Separation in Plexcitonic CdSe/Au and CdSe/Pt Nanorods

Abstract: Combining metal and semiconducting nanomaterials into one single nanocrystal, metal−semiconducting nanocomposites have been attracting considerable research interest due to the integrated and unprecedented properties that arise at the heterostructure interface. Herein, the dynamics of photoexcited charge carriers in CdSe/Au and CdSe/Pt nanorods is probed via ultrafast spectroscopy. Upon 400 nm photoexcitation, the results show both hot and cold electrons transfer from CdSe to the metal counterpart. The injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 27 publications
8
91
0
Order By: Relevance
“…Under visible light illumination, the photogenerated electrons and holes were excited from the VB and CB of g-C 3 N 4 and then transfer to the VB and CB of CaIn 2 S 4 , respectively. Due to the high Fermi level of metallic noble metal Pt, 43 it can serve as a photoexcited electron acceptor, which could induce the photoexcited electrons fast transfer to the loaded Pt cocatalyst to generate H 2 . 44−46 Our observation is similar to the result by Guo and co-workers, who demonstrated that ZnFe 2 O 4 /g-C 3 N 4 with type I band alignment shows the enhanced photoinduced electrons and holes separation efficiency and enhanced photocatalytic H 2 generation activity.…”
Section: Resultsmentioning
confidence: 99%
“…Under visible light illumination, the photogenerated electrons and holes were excited from the VB and CB of g-C 3 N 4 and then transfer to the VB and CB of CaIn 2 S 4 , respectively. Due to the high Fermi level of metallic noble metal Pt, 43 it can serve as a photoexcited electron acceptor, which could induce the photoexcited electrons fast transfer to the loaded Pt cocatalyst to generate H 2 . 44−46 Our observation is similar to the result by Guo and co-workers, who demonstrated that ZnFe 2 O 4 /g-C 3 N 4 with type I band alignment shows the enhanced photoinduced electrons and holes separation efficiency and enhanced photocatalytic H 2 generation activity.…”
Section: Resultsmentioning
confidence: 99%
“…We observed ultrafast quenching (<100 fs) of excitons in the CdSe NR by the Au tips ( fig. S5), consistent with previous results for related CdSe-Au NRs (33). In contrast to the pronounced broadening of the Au plasmon band, changes in the CdSe exciton bands were not apparent (Fig.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…[59][60][61][62] In solution based studies, HNPs with Pt domains were shown to more efficiently separate and transfer photogenerated charge carriers compared to hybrids with other metals. 58,[63][64][65][66] The advantage of Pt-CdSe and Pt-ZnO HNPs compared to those with Au is a reduced charging of the metal domains in combination with an efficient transfer of electrons towards redox active species in the surrounding reaction medium. 58,66 In CdSe, for example, a faster charge transfer from semiconductor to Pt than to Au caused by an altered interface barrier is in accordance with properties of macroscopic contacts between these materials: a lower Schottky barrier has been observed with the first material combination.…”
Section: Oligomeric Pt-cdse Hybrid Nanoparticlesmentioning
confidence: 99%
“…58,[63][64][65][66] The advantage of Pt-CdSe and Pt-ZnO HNPs compared to those with Au is a reduced charging of the metal domains in combination with an efficient transfer of electrons towards redox active species in the surrounding reaction medium. 58,66 In CdSe, for example, a faster charge transfer from semiconductor to Pt than to Au caused by an altered interface barrier is in accordance with properties of macroscopic contacts between these materials: a lower Schottky barrier has been observed with the first material combination. 67 Fast transfer of the 5 electrons that have been photogenerated in the semiconductor towards the metallic domain can be expected to reduce the recombination probability of the charge carriers and thus, be beneficial for light-charge transducer devices like photodetectors and solar cells.…”
Section: Oligomeric Pt-cdse Hybrid Nanoparticlesmentioning
confidence: 99%